Sejarah Etnis Tionghoa Dalam Dinamika Sosial Masyarakat Pulau Buru - Pattiasina, Johan (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2021)
The people who inhabit the island of Buru come from various places; among them, some groupings differentiate from one another and are known as Rana people, Wakahallo people, Orangakang, Earth lale people and traders. Of the five designations, this study focuses on